Indocyanine green angiography and the old question of vascular autonomy - Long term changes of microcirculation in microsurgically transplanted free flaps - Ludolph, Ingo; Arkudas, Andreas; Lang, Werner; Rother, Ulrich; Horch, Raymund E.; Cai, Aijia (Clinical Hemorheology and Microcirculation, 2019)
BACKGROUND: Free tissue transfer has become a routine procedure with low failure. In case of a compromised vascular pedicle, flap survival is time dependantly possible due to flap autonomization. However it remains unknown at what time and to which degree different factors influence flap autonomization.
CRIS-Team WoS Importer:2019-10-15